Inbreeding Depression on Morphological Markers in Mapanget Tall Coconut Line No. 32 - DONATA S. PANDIN (Buletin Palma, 2009)
The objective of this research was to determine inbreeding depression based on morphological markers in Mapanget Tall coconut line No.32. The result showed that inbreeding depression for vegetative characters in S2 generation was expressed only in girth of stem 100 cm from soil (3.28%) and width of leaflet (1.17%). Inbreding depression in S3 generation expressed in girth of stem 20 cm and 100 cm from soil (13.01% and 8.03%), height of 11 leafscars (11.80%), and number of leaflet (6.15%). In S4 generation , inbreeding depression expressed in girth of stem 20 cm and 100 cm from soil (5.39% & 14.41%), height of 11 leafscars (17.40%), width of leaflet (4.87%), and number of leaves (13.62%). Inbreeding depression also expressed in characters number of inflorescence per palm per year (7.41%), length of inflorescence stalk (34.18%), number of female flowers (21.32%), and length of male flowers bunch (10.84). In S3 generation inbreeding depression expressed in characters number of inflorescence per palm per year (14.90%), number of fruit per inflorescence (11.51%), length of inflorescence stalk (38.17%), number of female flowers (47.91%), and length of male flowers bunch (5.31%), but not expressed in width of inflorescence stalk (-11.07%) and thick of inflorescence stalk (-8.73%). Inbreeding depression expressed in S4 for all generatif characters ranged from 29.09% to 85.92%. In fruit components, inbreeding depression in S2 expressed in total fruit (9.01%), coconut water (16.07%), coconut shell (8.41%), and endosperm (7.55%) except on coconut fiber (-1.03%). In S3, inbreeding depression expressed in total fruit (5.20%), coconut fiber (0.58%), and endosperm (6.37%), except on coconut shell (-2.05%) and coconut water (-4.50%). In S4, inbreeding depression expressed in all characters of fruit component, total fruit (47.68%), coconut fiber (45.86%), coconut water (4.00%), coconut shell (51.82%), and endosperm (54.04%). Due to inbreeding depression, morphological performance of S4 generation nearly the same to that of Dwarf coconut.